2001
DOI: 10.1038/35078583
|View full text |Cite
|
Sign up to set email alerts
|

Direct, high-resolution measurement of furrow stiffening during division of adherent cells

Abstract: It is unclear whether cell division is driven by cortical relaxation outside the equatorial region or cortical contractility within the developing furrow alone. To approach this question, a technique is required that can monitor spatially-resolved changes in cortical stiffness with good time resolution. We employed atomic force microscopy (AFM), in force-mapping mode, to track dynamic changes in the stiffness of the cortex of adherent cultured cells along a single scan-line during M phase, from metaphase to cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
232
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(250 citation statements)
references
References 21 publications
14
232
2
2
Order By: Relevance
“…II C͒ suggested that G 2 M and native mitotic cells were stiffer than cells in the other phases. The increased stiffness of mitotic cells has been reported by other authors 32,33 and is associated with a reorganization of the cytoskeleton ͑Fig. 4͒.…”
Section: G Higher Stiffness Of Mitotic Cellsmentioning
confidence: 85%
“…II C͒ suggested that G 2 M and native mitotic cells were stiffer than cells in the other phases. The increased stiffness of mitotic cells has been reported by other authors 32,33 and is associated with a reorganization of the cytoskeleton ͑Fig. 4͒.…”
Section: G Higher Stiffness Of Mitotic Cellsmentioning
confidence: 85%
“…The prerequisite of imaging living cells in fluids is to attach them onto a flat support (such as glass) to withstand the lateral force exerted by the scanning tip. For those adherent cells, the most commonly used method is to directly culture them on a glass support for about 1-2 days and these cells can adhere to the support tightly [24]. Sometimes in order to enhance the cell adherence, adhesion proteins such as poly-L-lysine are coated onto the substrate [25].…”
Section: B-lymphoma Living Cell Imagingmentioning
confidence: 99%
“…Sacrificing two-dimensional resolution by using single line scans can increase time resolution while still capturing spatial information in one direction. The group of Radmacher used this trick to study the dynamics of 3T3 fibroblasts [1216], MTLn3 cells [1217], and potorous triactylis kidney cells [1218].…”
Section: Force Volume Modementioning
confidence: 99%